Felicidade e promoção de saúde em idosos: um estudo de revisão integrativa - Cairo, Nanci Garcia (2017)
Happiness has been the subject of studies in Psychology and has evidenced consistent relationships with physical and mental health in old age. The objective of this study was to systematize the knowledge produced between happiness and health promotion in elderly, from national and international articles, Portuguese and English, published from 2012 to 2016 in pre-established databases. The research identify gaps and broaden the knowledge of the subject in Brazil, as well as to find elements that guide future community practices with the elderly, having as reference the Community Social Psychology to discuss the results.Through the thematic analysis, two categories emerged among 30 selected publications: 1) Associations between happiness and health in elderly, and; 2) Factors related to happiness and health in elderly. The results showed that the five continents are involved with the theme and that several governmental associations are funding studies in the area. The researches pointed out the importance of considering happiness, both in the proposal of Brazilian and world public policies, and in the adoption of practices and strategies for a healthy aging.